Correction to: Anti-solvent materials enhanced structural and optical properties on ambiently fabricated perovskite thin films (Scientific Reports, (2024), 14, 1, (19995), 10.1038/s41598-024-70344-3) - Nur-E-Alam M.; Islam M.A.; Kar Y.B.; Kiong T.S.; Misran H.; Khandaker M.U.; Fouad Y.; Soudagar M.E.M.; Cuce E. (Nature Research, 2025)
Correction to: Scientific Reportshttps://doi.org/10.1038/s41598-024-70344-3, published:28 August 2024 The original version of this Article contained an error in the Acknowledgments section. The authors extend their appreciation to the Researchers Supporting Project number (RSPD2024R698), King Saud University, Riyadh, Saudi Arabia for funding this research work. This work was supported by the Malaysian Ministry of Higher Education through FRGS grant FRGS/1/2020/TK0/UM/02/33 and a Research Project under HICoE grant no. JPT.S(BPKI)2000/016/018/015JId.4 (21) / 2022003HICOE. The authors also like to acknowledge the academic support from the ISE, Universiti Tenaga Nasional, School of Science, Edith Cowan University, Australia, and the School of Engineering and Technology, Central Queensland University Australia." now reads: "The authors extend their appreciation to the Researchers Supporting Project number (RSPD2025R698), King Saud University, Riyadh, Saudi Arabia for funding this research work. This work was supported by the Malaysian Ministry of Higher Education through FRGS grant FRGS/1/2020/TK0/UM/02/33 and a Research Project under HICoE grant no. JPT.S(BPKI)2000/016/018/015JId.4 (21) / 2022003HICOE. The authors also like to acknowledge the academic support from the ISE, Universiti Tenaga Nasional, School of Science, Edith Cowan University, Australia, and the School of Engineering and Technology, Central Queensland University Australia." The original Article has been corrected. ? The Author(s) 2024.